ANALYSIS OF TIME MANAGEMENT AND EFFECTIVE COMMUNICATION TO THE EFFECTIVENESS OF DIGITAL MUSIC DISTRIBUTION PROCESS (CASE STUDY OF MUSIC AGGREGATOR IN PT. ALCOR KARYA GEMILANG JAKARTA) - Koerniawan Hidajat; David Kartono (SOSIOEDUKASI, 2026)
The purpose of this study is to analyze the Analysis of Time Management and Effective Communication on the Effectiveness of the Digital Music Distribution Process of PT. Alcor Karya Gemilang Jakarta. This study uses a quantitative approach with a survey method. The sampling technique used is available sampling, with a sample size of 33 respondents determined by utilizing the available subjects. Data collection was carried out through questionnaires distributed to all patients who came for treatment at each available polyclinic. Data analysis used the Partial Least Square – Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4 through outer model testing (outer loading, convergent validity, discriminant validity, cross loading, average variance extracted, composite reliability), inner model (R-square), and bootstrapping procedures to test the significance of the relationship between variables. The results of the study indicate that Time Management has a significant effect on the Effectiveness of the Digital Music Distribution Process, and Effective Communication has a significant effect on the Effectiveness of the Digital Music Distribution Process.